KONTRIBUSI HASIL BELAJAR CUSTOM MADE BERBASIS PROJECT BASED LEARNING TERHADAP KREATIVITAS SISWA TATA BUSANA - Goesly, Lonely Nisa Aziza Zenitha; Mariah, Siti; Sari, Anggri Sekar (Prosiding Pendidikan Teknik Boga Busana, 2023)
Study This aim For know Contribution results Study Making Custom Made Clothing based on Project Based Learning (X). Creativity Student (Y) in class XI fashion design at SMK Negeri 4 Yogyakarta Teachings 2022/2023. Type of research This is study descriptive quantitative. Population Study is student class XI fashion design, totaling 106 students. Research sample totaling 52 students use proportional random sampling technique with formula slovin . Data collection using questionnaire and documentation. Testing instrument done to 30 students outside sample but still in one population, validation test results use product moment correlation with n = 30 respondents of 20 items statement fall 3, reliability test using Cronbach's Alpha on variables creativity (Y) with mark coefficient 0.873. The data analysis technique uses descriptive tests and preceded product moment correlations with prerequisite tests namely the normality test and linearity test. Research results show that 1) There is contribution results Study making custom made clothing with application of project based learning to creativity student class XI field fashion expertise at SMK N 4 Yogyakarta 2022/2023 teaching amounted to 15.1%; 2) Learning outcomes making fashion custom made with application of project based learning in class XI fields fashion expertise _ in category competent with frequency relative 59.50%; 3) Creativity students in class XI fields fashion expertise _ including to in category currently with frequency relatively 61.50%.